2014
DOI: 10.1186/1471-2318-14-115
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in Iranian older adults who experienced fall during the past 12 months

Abstract: BackgroundPhysical activity may have several benefits for elderly people. However, the risk of falling might prevent this population from showing interest in physical activity. This research was aimed to explore facilitators and barriers to physical activity in older persons who have experienced at least one fall in the past 12 months.MethodsThis cross sectional study was conducted in 2010-2011, in Tehran, Iran. Using a multistage sampling method a group of elderly people entered into the study. A multi-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Along with the original version [7], there was no correlation between PASE and BMI in the current study, but there was a significant correlation between PASE and health status. Another study showed that, the higher PASE score is correlated with more favorable health [31, 32]. In the current study, the Cronbach's α coefficient indicating the good internal consistency.…”
Section: Discussionsupporting
confidence: 56%
“…Along with the original version [7], there was no correlation between PASE and BMI in the current study, but there was a significant correlation between PASE and health status. Another study showed that, the higher PASE score is correlated with more favorable health [31, 32]. In the current study, the Cronbach's α coefficient indicating the good internal consistency.…”
Section: Discussionsupporting
confidence: 56%
“…This is because of the activities they carry out, such as doing the housework, caring for their offspring and other family members (Salehi et al , 2010). Decreased risk of falling and physical activity were shown to be correlated by a previous study (Salehi et al , 2014). Furthermore, some research has also shown Iranian older women to be more energetic and emotionally resilient that their male counterparts (Salehi et al , 2012).…”
Section: Findings and Discussionsupporting
confidence: 56%
“…Data on physical activity was measured using Physical Activity Scale for Elderly (PASE) and was collected through interviews [17,18]. The validity and reliability of this questionnaire (Cronbach's alpha coefficient of 0.97) were evaluated in an Iranian study [19]. The total score for each individual was calculated as between 0 and 400; higher scores meant higher physical activity levels.…”
Section: Methodsmentioning
confidence: 99%